Pengaruh Model Problem Based Learning (PBL) Menggunakan Metode Demonstrasi dan Eksperimen pada Pembelajaran Fisika tentang Hukum Newton - Agnes Mayanti; Cosmas Poluakan; Farly Reynol Tumimomor (Charm Sains: Jurnal Pendidikan Fisika, 2022)
Learning physics is often seen as an abstract science presented in a theory that is less interesting and seems difficult, and assumes that physics is difficult to master and understand. With the PBL (problem based learning) learning model, it is expected to make a major contribution to students where students are able to master and understand a physics concept. The purpose of this study was to determine the effect of the PBL learning model using demonstration and experimental methods on learning outcomes of physics about Newton's law at SMK Anugrah Tondano in the odd semester of the 2019/2020 school year. This study used a posttest-only control group design. The treatment used in this experiment is a PBL learning model using demonstration and experimental methods. Analysis of the data used is normality test and statistical test with the help of SPSS 25 application. The results of this study indicate that the problem based learning (PBL) model has an effect on student learning outcomes.